2013
DOI: 10.1136/bmj.f7140
|View full text |Cite
|
Sign up to set email alerts
|

Medicalising unhappiness: new classification of depression risks more patients being put on drug treatment from which they will not benefit

Abstract: ANALYSIS Summary boxClinical context-Diagnoses of major depressive disorder and treatment with antidepressant drugs are increasing Diagnostic change-DSM-III homogenised the diagnosis of depression and the new DSM-5 classification broadens the definition further, allowing the diagnosis of major depressive disorder just two weeks after bereavement Rationale for change-To provide more patients with access to effective treatments Leap of faith-Accurate diagnosis of mild depression is possible; treatment is necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 43 publications
(28 reference statements)
0
108
0
7
Order By: Relevance
“…It is possible that the incidence of depression is overestimated if the only measure of depression is a physician's diagnosis (which may even reflect a tendency for over-diagnosis of depression by GPs, e.g. see Dowrick & Frances, 2013). What's more, this type of measure provides no information regarding date of symptom onset and possible triggering factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the incidence of depression is overestimated if the only measure of depression is a physician's diagnosis (which may even reflect a tendency for over-diagnosis of depression by GPs, e.g. see Dowrick & Frances, 2013). What's more, this type of measure provides no information regarding date of symptom onset and possible triggering factors.…”
Section: Discussionmentioning
confidence: 99%
“…The finding may also represent an over-prescribing trend by GPs. A relatively recent meta-analysis showed that while GPs were good at ruling out appropriately a diagnosis of depression, the modest prevalence of depression in primary care leads to a high proportion of misclassifications and the potential for over treatment with a rate of false positives that outnumber true positives by about 50% [44,45]. It is possible also that the finding represents a group of patients who have been correctly diagnosed and who are being appropriately treated with a medication that has been effective in treating their symptoms and, therefore, in lowering their GHQ-12 scores.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,4 In low-and middle-income countries (LMICs), the focus of research has been on the treatment gap, the inequalities in mental health systems, and scaling up access to medical expertise and treatment through task shifting. Whilst these are key considerations, the issues need to be seen through a broader lens that includes the family, community, and social determinants of health and cultural contexts.…”
Section: Introductionmentioning
confidence: 99%